Comparative evaluation of efficacy of EndoVac irrigation system to Max-I probe in removing smear layer in apical 1 mm and 3 mm of root canal: An in vitro scanning electron microscope study - Ankur Dua; Deepti Dua (Wolters Kluwer Medknow Publications, 2015)
Background: The purpose of this study was to compare the efficacy of EndoVac irrigation system and side-vented closed ended needle (Max-I probe) in removing smear layer from root canals at 1 mm and 3 mm from working length using ProTaper rotary instrumentation. Materials and Methods: A total of 50 freshly extracted maxillary central incisors were randomly divided into two groups after complete cleaning and shaping with ProTaper rotary files. In one group, final irrigation was performed with EndoVac system while in other group, final irrigation was done with a 30 gauge Max-I probe. 3% sodium hypochlorite (NaOCl) and 17% ethylenediaminetetracetic acid were used as final irrigants in all teeth. During instrumentation, 1 ml of 3% NaOCl was used for irrigation after each rotary instrument in the similar manner as in final irrigation. After instrumentation and irrigation, teeth were sectioned longitudinally into buccal and palatal halves and viewed under scanning electron microscope for evaluation of smear layer. Statistical analysis was performed using Kruskal-Wallis and Mann-Whitney U-test. (P < 0.05) Results: At 3 mm level, there was no significant difference between two groups. At 1 mm level, EndoVac group showed significantly better smear layer removal compared with Max-I probe (P = 0.0001). Conclusion: EndoVac system results in better smear layer removal at 1 mm from working length when compared to Max-I probe irrigation.